Суб’єкти контролю якості аудиту в Україні - Шалімова, Н. С.; Shalimova, N. (КНТУ, 2009)
В статті досліджені основні групи суб’єктів контролю якості аудиту в Україні. Проаналізовані їх функції, повноваження та можливості впливу на якість аудиту. Виділені недоліки системи контролю якості аудиту з урахуванням вимог європейського законодавства, вирішення яких є важливим чинником підвищення якості аудиту. The principal groups of subjects of audit quality control in Ukraine have been considered in the article. Their functions, authority and means of influence on audit quality have been analyzed. The shortcomings of audit quality control system settlement of which is a significant factor of increasing the audit quality taking into account the euro-integrating course of Ukraine were singled out.
Subjects of audit quality control in Ukraine
Keywords: аудит; система контролю якості аудиту; суб’єкти контролю якості аудиту